Population of the Armenian Higlands in the age of Antiquity (according of anthropological materials of urban and rural settlements) - A.Yu. Khudaverdyan; A.A. Hovhanisyan; A.A. Yengibaryan; R.Sh. Matevosyan; G.G. Qocharyan; P.S. Palanjan; L.G. Eganyan; A.A. Khachatryan (Вестник археологии, антропологии и этнографии, 2020)
Article is devoted to studying of bone remains from antique burial grounds from the territory of the Armenian Highland. Anthropological materials of burials consist of 322 skeletons and dated I–III c. AD. The article analyzes the differences in anthropological characteristics of urban and rural population of Armenia of Antiquity period. The work is based on classical craniometric and statistical research methods. Artificial cranial deformationare and unintended deformation of a cradle-type found among urban and rural populations. As an intragroup analysis showed, the main differences between male urban and rural population across the size of the width of the frontal bone and face. If the villagers face orthognatic, angle of horizontal profiling at the top level enters the category of averages, in urban women face mezognatik, the angle of horizontal profiling is characterized by small values. Intergroup analysis showed, closest to urban male groups it turned out the tribes of Chernyakhov culture and the population of the Middle East. A male part of the villagers shows intimacy with Scythians of Crimea, Ukraine and Transnistria. The female part of the towns’ people is close with the Scythians of Ukraine and Crim; villagers are morphologically similar to the carriers of the Middle Sarmatian cultures of the Don region, with a population of the first centuries AD from Tanais, European and Asian Bosporus. Morphological analogies with the population of Northern Turkmenistan (Tumek-Kichidzhik), Western Ukraine (Chernyakhov culture), Middle Dnieper and Moldova (Scythians) were also revealed. This circumstance confirms the fact of sustainable, constant migration flow to the territory of the Armenian Highlands.